2011
DOI: 10.1097/ede.0b013e3182093a0f
|View full text |Cite
|
Sign up to set email alerts
|

Time-window Bias in Case-control Studies

Abstract: Time-related biases in cohort studies can produce illusory "beneficial" effects of medications due entirely to an artifact of the analytic design. We describe "time-window bias" in the context of a case-control study, reporting that statin use was associated with a 45% reduction in the incidence of lung cancer. This bias results from the use of time-windows of different lengths between cases and controls to define time-dependent exposures. We illustrate the bias using a population of 365,467 patients from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 12 publications
1
102
0
Order By: Relevance
“…The comparison of these two groups may introduce immortal time bias 17,22,23 . We conducted similar analyses in our data by classifying eligible individuals as initiators if they initiated statin therapy anytime during the first 6 months of follow-up and as non-initiators otherwise.…”
Section: Methodsmentioning
confidence: 99%
“…The comparison of these two groups may introduce immortal time bias 17,22,23 . We conducted similar analyses in our data by classifying eligible individuals as initiators if they initiated statin therapy anytime during the first 6 months of follow-up and as non-initiators otherwise.…”
Section: Methodsmentioning
confidence: 99%
“…If this condition is not met, the 'time-window bias', an error that is still frequent in observational research, will usually result in a biased estimate of the exposure effect. 2 In clinical practice, medication non-adherence is one of the main factors that reduce the effectiveness of drug therapies; 1 therefore, the aim of this study was to evaluate the impact of the time-window bias when the exposure is a measure of medication adherence. In this setting, we found that this bias produces an underestimate of the beneficial effect of good medication adherence that conforms to clinical guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…3 This method assigns the same length of observation to cases and to their matched controls to ensure equal time windows to measure exposure. 2 No studies have measured how the time-window bias affects assessments of the effect of medication adherence on health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies that compare long-acting insulin analogs to nonbasal insulin may introduce confounding by disease duration. Time-window bias occurs when the opportunity for exposure differs between case subjects and control subjects (29,43).…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%